Learned patriots debating science, state, and society in the nineteenth- century Ottoman Empire - Yalçınkaya, M. Alper (University of Chicago Press, 2015)
The nineteenth century was, for many societies, a period of coming to grips with the growing, and seemingly unstoppable, domination of the world by the "Great Powers" of Europe. This book examines what it meant for nineteenth-century Ottoman elites themselves to have a debate about science.